2004
DOI: 10.1111/j.1365-2966.2004.07483.x
|View full text |Cite
|
Sign up to set email alerts
|

GHASP: an Hα kinematic survey of spiral and irregular galaxies – III. 15 new velocity fields and study of 46 rotation curves

Abstract: We present Fabry–Pérot observations obtained in the frame of the GHASP survey (Gassendi HAlpha survey of SPirals). We have derived the Hα maps, the velocity fields and the rotation curves for a set of 15 galaxies. The data presented in this paper are combined with the data published in our two previous papers in order to make a preliminary analysis of the rotation curves obtained for 46 galaxies. We check the consistency of our data with the Tully–Fisher relationship and conclude that our Hα rotation curves re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…Analysing photometric observations, Coccato et al (2004) do not confirm the presence of a bar, but find a strong velocity gradient along the minor axis of the galaxy in their long-slit data. Using Fabry-Pérot spectroscopy, Garrido et al (2004) found a characteristic kinematical feature at the end of the assumed bar, the extent of which they estimate to be 30 in projection. Either NGC 2541 possesses a small bar or an inclined inner disk at the innermost radii.…”
Section: The Galaxies Studiedmentioning
confidence: 99%
“…Analysing photometric observations, Coccato et al (2004) do not confirm the presence of a bar, but find a strong velocity gradient along the minor axis of the galaxy in their long-slit data. Using Fabry-Pérot spectroscopy, Garrido et al (2004) found a characteristic kinematical feature at the end of the assumed bar, the extent of which they estimate to be 30 in projection. Either NGC 2541 possesses a small bar or an inclined inner disk at the innermost radii.…”
Section: The Galaxies Studiedmentioning
confidence: 99%
“…We supplemented our sample by adding host galaxies whose rotation sense was determined from the spectroscopic observations in the literature (Rubin et al 1982(Rubin et al , 1985(Rubin et al , 1999Broeils & van Woerden 1994;Han et al 1995;Taylor et al 1995;Rhee & van Albada 1996;Zaritsky et al 1997;Sofue 1997;Sofue et al 1997Sofue et al , 1998Sofue et al , 2003Héraudeau & Simien 1998;Héraudeau et al 1999;Vega Beltrán et al 2001;Garrido et al 2002Garrido et al , 2003Garrido et al , 2004Garrido et al , 2005Vogt et al 2004;Coccato et al 2004;Fridman et al 2005;Hernandez et al 2005;Noordermeer et al 2005;Chemin et al 2006;Falcón-Barroso et al 2006;Daigle et al 2006;Ganda et al 2006;Azzaro et al 2006;Herbert-Fort et al 2008;Epinat et al 2008aEpinat et al , 2008bSwaters et al 2009). We compiled 390 satellites associated with 116 hosts.…”
Section: Spin Direction Of Host Galaxiesmentioning
confidence: 99%
“…At low redshifts, the knowledge of 2D velocity fields has proved to be a powerful kinematical tool to investigate the properties of nearby galaxies (Östlin et al 2001;Veilleux et al 2001;Swinbank et al 2003;Mendes de Oliveira et al 2003;Garrido et al 2004;Epinat et al 2008a,b). The velocity fields of galaxies at intermediate redshift (0.4 < z < 0.75) have been investigated using FLAMES/GIRAFFE at VLT Puech et al 2006;Yang et al 2008;Neichel et al 2008;Puech et al 2008).…”
Section: Introductionmentioning
confidence: 99%